2000
DOI: 10.1093/jnci/92.11.918
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutation Screening: Identification of Individuals Harboring K-ras Mutations With the Use of Plasma DNA

Abstract: Plasma DNA assays for the detection of mutations in K-ras codon 12 may provide a feasible method to screen populations for somatic mutations frequently found in neoplasms. The clinical utility of using this test in screening populations requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 25 publications
7
66
0
8
Order By: Relevance
“…The phospho-ERK activation is in addition to the constitutive levels stimulated by oncogenic RAS in these cells (Fig. 4), as FET colon cancer cells contain a mutated K-RAS gene (codon 12 mutation: GGT>GCT) [6], making K-RAS constitutively active. BMP2 activation of phospho-ERK may act as a "brake" on BMP-induced growth suppression by regulating or limiting this response in the correct setting.…”
Section: Bmp-smad Signaling and Growth Suppression Is Modulated By K-mentioning
confidence: 99%
See 1 more Smart Citation
“…The phospho-ERK activation is in addition to the constitutive levels stimulated by oncogenic RAS in these cells (Fig. 4), as FET colon cancer cells contain a mutated K-RAS gene (codon 12 mutation: GGT>GCT) [6], making K-RAS constitutively active. BMP2 activation of phospho-ERK may act as a "brake" on BMP-induced growth suppression by regulating or limiting this response in the correct setting.…”
Section: Bmp-smad Signaling and Growth Suppression Is Modulated By K-mentioning
confidence: 99%
“…A common finding in colonic neoplasms is activation of RAS and its downstream effectors [6,7]. RAS proteins are proto-oncogenes involved in a variety of signal transduction pathways that normally regulate cellular proliferation, differentiation and death.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The same somatic mutations in oncogenes or tumor suppressor genes such as K-ras or p53 that are present in primary tumors were also detected in the circulating cell-free DNA samples of patients with cancer. [7][8][9] Additionally, the cancer-specific hypermethylation of the p16INK4A, CDH1, and DAPK1 promoter regions in plasma DNA isolated from patients with cancer suggested that circulating methylated DNA could be used as a diagnostic and prognostic marker for the disease. 10 -12 While the quantification of plasma DNA has been proposed as a diagnostic tool for cancer, current results suggest that additional controlled studies are required to establish this possibility.…”
mentioning
confidence: 99%
“…При пороговом значении уровня опухолевой цДНК в 4,86 нг/мл чувствительность и специфичность метода составили 78,52 и 86,08 % соответственно [29]. Аналогичные результаты получены и другими исследо-вательскими группами [14,[30][31][32].…”
unclassified
“…При этом в 1-м исследова-нии совпадение по мутационному статусу гена и пер-вичной опухоли отмечено в 83 %, «дикий» же тип гена в первичной опухоли в 93 % случаев сопровождался и отсутствием мутации в цДНК. Во 2-м исследовании чувствительность метода оказалась низкой: если в цДНК мутация в гене KRAS была выявлена у 8,5 % больных, то в первичной опухоли она выявлялась уже у 41,0 % [32,52]. В других исследованиях, проведенных в конце 90-х годов прошлого века, частота соответствия мута-ционного статуса гена KRAS в цДНК и опухолевом ма-териале варьирует от 19 до 86 % [4,53,54].…”
unclassified